Relationship of Lutein and Zeaxanthin Levels to Neurocognitive Functioning: An fMRI Study of Older Adults. (25th October 2016) - Lindbergh, Cutter A.; Mewborn, Catherine M.; Hammond, Billy R.; Renzi-Hammond, Lisa M.; Curran-Celentano, Joanne M.; Miller, L. Stephen
Abstract: Objectives: It is well known that the carotenoids lutein (L) and zeaxanthin (Z) improve eye health and an accumulating evidence base suggests cognitive benefits as well. The present study investigated underlying neural mechanisms using functional magnetic resonance imaging (fMRI). It was hypothesized that lower L and Z concentrations would be associated with neurobiological inefficiency (i.e., increased activation) during cognitive performance.Methods: Forty-three community-dwelling older adults (mean age=72 years; 58% female; 100% Caucasian) were asked to learn and recall pairs of unrelated words in an fMRI-adapted paradigm. L and Z levels were measured in retina (macular pigment optical density) and serum using validated procedures.Results: Following first-level contrasts of encoding and retrieval trials minus control trials ( p <.05, family-wise error corrected, minimum voxel cluster=8), L and Z were found to significantly and negatively relate to blood-oxygen-level-dependent signal in central and parietal operculum cortex, inferior frontal gyrus, supramarginal gyrus, planum polare, frontal and middle temporal gyrus, superior parietal lobule, postcentral gyrus, precentral gyrus, occipital cortex bilaterally, and cerebellar regions.Conclusions: To the authors' knowledge, the present study represents the first attempt to investigate neural mechanisms underlying the relation of L and Z to cognition using fMRI. The observed results suggest that L and Z promote cognitive functioning in old age by enhancing neural efficiency. ( JINS, 2017, 23, 11–22)